Kajian Ekologi Serdang (Livistona sp.) di Kecamatan Sungai Gelam Kabupaten Muaro Jambi: Ecology of Serdang (Livistona sp.) in Sungai Gelam District, Muaro Jambi Regency - Nursanti, Nursanti; Wulan, Cory; Puri, Suci Ratna; Albayudi, Albayudi (Jurnal Silva Tropika, 2024)
Spread of Livistona sp. located in Sungai Gelam Subdistrict, Muaro Jambi Regency in Parit Village, Petaling Jaya Village, Sungai Gelam Village which is the location where this research will be carried out because at that location there are still Livistona sp. The environmental requirements for growing Livistona sp. It is a healthy environment that must be composed of several components with supporting conditions, both physical and biotic components. Therefore, it is important to study the ecology of Serdang (Livistona sp.) in order to provide information that can be used in the sustainable management of these plant species. The ShannonWieners exposure value for plants other than serdang in Parit Village at the seedling level had a value of 2,596 (medium advertising category), 2,887 saplings (medium advertising category), 0,679 poles (low advertising category), 0,461 trees (low advertising category). For biodiversity other than serdang on line two in Petaling Jaya Village at the seedling level it has a value of 2,851 (medium category), 3,001 stakes (medium category), 1,707 poles medium category, trees 1,318 (medium category). The diversity of plants other than serdang on line three in Sungai Gelam Village at the seedling level had a value of 2,196 (moderate diversity category), saplings 2,076 (medium category category), poles and trees 0.596, 0.324 (low category category). Ecological factors around serdang plants for the humidity range of 290C – 30,370C. The condition of the soil at the study site is sandy soil with a pH of 3.75 – 4.89, light intensity ranges from 1137 Lux – 9518 Lux, the amount of light intensity can be affected by vegetation cover. The slope of the place where the prawns grow is between 2% and 4%, which means that the sedge grows on a gentle to slightly steep slope.